AN ASSESSMENT OF HIV/AIDS ON AGE AND DIFFERENTIALS IN GENDER USING REGRESSION METHOD - A, ADAMU; A. U. SHELLENG; A. U. KINAFA (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
HIV/AIDS is a contagious disease as a result of unprotected sex or through blood transfusion or through sharing of sharp objects. When first infected. A person can develop an acute infection which can range in severity from a very mild illness with few or no symptoms to a serious condition requiring hospitalization. Acute HIV/AIDS can manifest within the first 6 months of contacting the disease. The disease become one of the factors for the death of many people in our society for over 3 decades. The method used for this study is multiple regression method and t-test. The data was secondary collected from the record department of Gombe specialist hospital for a period of ten years from 2008 – 2017. The result of this study shows that, there is significance difference in both gender and age. Such we conclude that gender and age contributed immensely in the spread of HIV/AIDS. Majority of the victims are female, also almost 88% of the victims are youth of the age 0 – 49 years while elders constitute the remaining percent. Hence, from the result, government and non-governmental organization need to embark on mass awareness and sensitization campaign to all nook and crannies of the state with a target of reducing the risk of contracting the disease.